#TITLE_ALTERNATIVE# - DWI ANGGA (NIM 12103043), MAHETA
In line with the development of this era, the advance in technology and the growth needs on petroleum and gasses, the exploration and exploitation of these products head to drilling operation under the sea. In this case, offshore pipeline is an essential transportation means to distribute petroleum and gasses from the source to the processing site. Due to the irregular topography on the seabed, the offshore pipeline will be likely to have a free span. The evaluation standards on free span are diverse and so are the results. One type of free span analysis is an analysis which is based on static loading. This static loading analysis is carried out by using two methods, Mousselli and Finite Element Method. Mouselli Method is a method which is accomplished analytically employing dimensionless plot, while Finite Element Method is carried out using a software based finite element analysis. The analysis employing Mousselli Method for low depression case obtains maximum allowable free span length up to 122,89 m, while Finite Element Method reaches 119,5 m. Based on this calculation, Mousselli Method is slightly included into plastic area. In the case of elevated obstruction, maximum allowable free span length in Mousselli Method is 155,3 m, while in Finite Element Method is 102,4 m. The analytical results employing Mousselli and Finite Element Method illustrate that the influence of diameter variety, thickness, internal and external pressure tends to have equal results toward maximum allowable free span length. In addition, the existence of support decreases maximum stress that occurs.